Double Exposure and Fractal City: Cultural Disengagement and Disembodied Belonging due to Outdoor Thermal Changes - Alam, Meredian (Journal of Regional and City Planning, 2018)
Abstract. The irresistible global phenomenon of climate change is widely known as an emerging challenge that threatens the sustainability of public life. This article examines climate change complexities in urban areas of Indonesia, particularly those that are the result of massive urban infrastructure development. In Indonesia, urban infrastructure development has been observed to have reduced the number of open green spaces, resulting in increased temperatures, primarily in city areas. This environmental issue is exacerbated by the presence of prolonged drought due to El NiÃ±o. Several studies have demonstrated that climate change causes mental disorders among urban residents, characterized by emotional and cultural disengagement from their place of residence, clinically called âsolastalgiaâ. This term was coined by Professor Glenn Albrecht, an Australian environmentalist, formerly based in Newcastle NSW. This study examined the concept of solastalgia through ethnographic interviews with five young people who have permanently lived in the city of Yogyakarta, Indonesia for more than 20 years. This study captures their personal solastalgia experiences resulting from climate change complexities. Solastalgia, as confirmed by the respondents, covers various socio-cultural symptoms like social tension, immobility, distress, and future insecurity. The narratives of the respondents indicate that climate change in addition to urban infrastructure development has uprooted their belongingness to the city, valued by them as a space for communal cultural identity formation. Subsequently, after analyzing their subjective experiences, this study confirms that spatial development of the urban area of Yogyakarta in favor of the economy neglects the future of young people.Keywords.Â  solastalgia, climate change, urban, Yogyakarta City.Abstrak. Perubahan iklim sebagai fenomena global yang tidak bisa dihindarkan telah dikenal luas sebagai tantangan yang muncul terhadap keberlangsungan kehidupan publik dewasa ini. Artikel ini mengkaji kompleksitas perubahan iklim di daerah perkotaan di Indonesia, terutama yang merupakan efek dari pembangunan infrastruktur besar-besaranÂ  di perkotaan.. Pembangunan infrastruktur perkotaan telah mengurangi ruang terbuka hijau dan mengakibatkan peningkatan suhu, terutama di wilayah perkotaan. Masalah lingkungan di wilayah ini diperparah oleh adanya kekeringan berkepanjangan akibat El NiÃ±o di Indonesia. Beberapa penelitian menunjukkan bahwa fenomena perubahan iklim telah menyebabkan gangguan mental pada penduduk perkotaan, ditandai dengan diskoneksi emosi dan kultural dengan tempat tinggal mereka, yang secara klinis disebut sebagai Solastalgia. Istilah ini diciptakan oleh Profesor Glenn Albrecht, aktivis lingkungan Australia, yang sebelumnya berbasis di Newcastle NSW. Konsep ini digali melalui wawancara etnografi dengan lima orang muda yang telah hidup secara permanen selama lebih dari 20 tahun di kota Yogyakarta, Indonesia. Studi ini menangkap Solastalgia sebagai pengalaman mereka menghadapi kompleksitas dalam pembangunan di perkotaan. . Solastalgia, sebagaimana diinformasikan oleh responden, mencakup berbagai gejala sosial-budaya seperti ketegangan sosial, imobilitas, marabahaya, dan keamanan masa depan. Narasi para responden ini menunjukkan bahwa perubahan iklim, di samping pembangunan infrastruktur perkotaan, telah mencabut kepemilikan mereka terhadap kota, yang dihargai oleh mereka sebagai ruang untuk pembentukan identitas budaya komunal. Selanjutnya, selain menganalisis pengalaman subyektif mereka, penelitian ini menegaskan bahwa pengembangan spasial dari daerah perkotaan yang mendukung ekonomi mengabaikan masa depan orang muda.Kata Kunci. solastalgia, climate change, urban, Yogyakarta City.